Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcell.2022.998328
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and treatment of neuropsychiatric systemic lupus erythematosus: A review

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease with a complex pathogenesis. Neuropsychiatric systemic lupus erythematosus (NPSLE) is a serious complication of SLE that involves the nervous system and produces neurological or psychiatric symptoms. After decades of research, it is now believed that the diverse clinical manifestations of NPSLE are associated with intricate mechanisms, and that genetic factors, blood-brain barrier dysfunction, vascular lesions, multiple autoimmune antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 74 publications
1
41
0
Order By: Relevance
“…In regards to wasp stings, a report comparing HP + continuous venovenous hemodiafiltration (CVVHDF) versus TPE + CVVHDF, found no difference in survival (Yuan, 2016). However, a retrospective study of patients with at least 30 wasp stings observed TPE reduced mortality compared to continuous venovenous hemofiltration or HP (Liu, 2022). Patients with snakebites may develop a thrombotic microangiopathy (TMA).…”
Section: Rationale For Therapeutic Apheresismentioning
confidence: 99%
“…In regards to wasp stings, a report comparing HP + continuous venovenous hemodiafiltration (CVVHDF) versus TPE + CVVHDF, found no difference in survival (Yuan, 2016). However, a retrospective study of patients with at least 30 wasp stings observed TPE reduced mortality compared to continuous venovenous hemofiltration or HP (Liu, 2022). Patients with snakebites may develop a thrombotic microangiopathy (TMA).…”
Section: Rationale For Therapeutic Apheresismentioning
confidence: 99%
“…Various serum markers [interleukin (IL)-6, interferon alpha (IFN-α), microRNA(miR)-23a, miR-155, neuron specific enolase, S100A8/A9], CSF markers [IL-6, IL-10, IL-13, IL-18, neopterin, IFN-α, granulocyte colony stimulating factor (G-CSF)], and serum/CSF antibodies [anti-NDMAR, anti-RP, anti-ganglioside, anti-microtubule associated protein 2 (anti-MAP2), anti-glial fibrillary acidic protein (anti-GFAP)] have all been postulated. 23,[49][50][51][52] Similarly, recent aptamer-based screening of CSF in NPSLE patients has revealed several promising biomarkers, including lipocalin 2, macrophage colony stimulating factor (M-CSF), IgM and complement C3. 50 Their availability for clinical use in the future could help define pathogenesis, target treatments, and improve prognosis.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is an autoimmune disease with systemic implications that can affect multiple organisms. Psychiatric manifestations represent a complication of this condition, a phenomenon known as neuropsychiatric systemic lupus erythematosus (NPSLE) directly related to SLE [ 1 ]. NPSLE could be the singular or initial manifestation of SLE, and in roughly 30% of individuals with neuropsychiatric symptoms, SLE is the direct cause.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, molecular elements associated with coagulopathy which may cause a neurodegenerative response, are also investigated, in addition to the inflammatory autoimmune response. Still, essential elements are also identified that intervene in the blood barrier of the central nervous system, affecting the permeability and allowing the penetration of specific autoantibodies and immune cells in the central nervous system with mediated neuronal damage [ 1 ]. Two paths of pathological mechanisms that may contribute to SLE’s neuropsychiatric manifestations have been identified and addressed in the specialized literature [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation